EFEKTIVITAS PSIKOEDUKASI MORAL ENGAGEMENT DI SMA MUHAMMADIYAH 3 TULANGAN DALAM MENURUNKAN BULLYING PADA SISWA - Zidan, Muhammad Zidanil Ilmi Naf'an Munif; Laili, Nurfi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to measure the effect of moral engagement psychoeducation on reducing bullying behavior among students at SMA Muhammadiyah 3 Tulangan. The research method used was quantitative experimentation with a student population of 35 people. The sampling technique used is saturated sampling. The scale used to measure bullying behavior is a pre-test and post-test scale compiled by researchers, while to measure moral engagement the Comprehensive School Climate Inventory (CSCI) is used. The analysis technique used is paired sample t-test using JASP software version 0.18. The research results showed that there was a significant difference between the pre-test and post-test results after being given moral engagement psychoeducation (t(34) = -5.619; p < 0.001). These results prove that moral engagement psychoeducation can reduce bullying behavior in students and increase moral engagement in the school environment.